Critical theory and its contribution to the nursing discipline - Angélica Mosqueda-Díaz; Vivian Vílchez-Barboza; Sandra Valenzuela-Suazo; Olivia Sanhueza-Alvarado (Universidad de Antioquia, 2014)
This article reflects on the Critical theory, stemming from the most important philosophical concepts and the modifications it has endured over time. Thereafter, we expose the contribution of the Critical theory to Nursing. This emphasizes on the contextual analysis of the phenomena and it is a self-critique to prevent dogmatisms and totalitarianisms. It postulates that in order to establish a truth, we must consider the historical conditions within which said truth emerges. Jürgen Habermas, with his Theory of Communicative Action, reorients the original postulates of the Critical theory, making it more coherent from the social point of view, through the Guiding Interests of Knowledge. Nursing professionals who follow the Critical theory highlight the need to improve the description of the construction of knowledge with an emancipating and liberating purpose, which permits Nursing to provide responses to approach reality through a global and dialectic vision and from a democratic position of knowledge, construct research from the social situational reality that is part of its daily experience; everything that can be unified as a "Philosophy of Nursing Care", which should be incorporated onto the professional formation of the discipline and onto the research area.